EFFECTIVE METHODOLOGICAL APPROACHES TO TEACHING THE PROPER AND SAFE USE OF LABORATORY GLASSWARE IN CHEMISTRY EDUCATION - Urazbayeva , Gulnoza (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Laboratory sessions are an integral part of chemistry education, providing students with the opportunity to integrate theoretical knowledge with practical skills. In this process, glassware plays a central role, as it is used in nearly all experiments [1]. The correct selection, use, and storage of glassware ensure not only the accuracy and reliability of experimental results but also laboratory safety. Therefore, it is essential for students to thoroughly learn the proper procedures for handling glassware